Penerapan teknik self management terhadap perilaku menyimpang remaja penggemar game online - Ati Sulastri; Eni Nur'aeni (Program Studi Bimbingan Konseling Islam Fakultas Dakwah Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
Abstract:Now humans have experienced the development of an increasingly modern era. Problems of deviant behavior by online game fans are certainly different, so research still needs to be done to explore data about the conditions of deviant behavior of online game fans in Cibongkok Village. The aims of this study are to analyze the deviant behavior that occurs in adolescents who are fans of online games in Cibongkok Village. To determine the application of self-management techniques in reducing the deviant behavior of adolescent online game fans in Cibongkok Village. Researchers use a type of descriptive qualitative. The respondents were 4 teenagers who like to play online games in Cibongkok Village, Mekarsari Village, Cinangka District, Serang Regency, Banten Province. Based on the research that has been done, it can be concluded that deviant behavior committed by adolescents who are fans of online games, namely all respondents uttered foul language and said dirty words, two respondents did not do their schoolwork, two teenagers gambled online games and one teenager stole people's money old. The results of applying self-management techniques to reduce the deviant behavior of adolescent online game fans had a good effect on three respondents and had no effect on one respondent.Keywords: self-management techniques, deviant behavior, online game fans.